2015
DOI: 10.1108/k-10-2013-0230
|View full text |Cite
|
Sign up to set email alerts
|

A managerial application of system dynamics modeling to outsourcing

Abstract: Purpose -The purpose of this paper is to use modeling and simulation to investigate the puzzling performance problems that plagued the project outsourcing in term of poor quality and delivery delay, and apply the appeal and power of system dynamics modeling as a managerial approach to improve learning and intervention in complex situations to South African context where little or no such attempt had been made. Design/methodology/approach -This work is based on exploratory use of system dynamics modeling to stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The results of this study were consistent with studies such as Lisse (2014), Block and Pickl (2014), Ojugbele and Bodhanya (2015), Shiboud and Assaf (2019), and the results of Al Hallak et al (2019). In researches that have consistent results, they point out that Outsourcing should be done very cautious.…”
Section: K 499supporting
confidence: 91%
See 3 more Smart Citations
“…The results of this study were consistent with studies such as Lisse (2014), Block and Pickl (2014), Ojugbele and Bodhanya (2015), Shiboud and Assaf (2019), and the results of Al Hallak et al (2019). In researches that have consistent results, they point out that Outsourcing should be done very cautious.…”
Section: K 499supporting
confidence: 91%
“…Integration of this approach with a dynamic model which is for prediction of future can able the researchers to formulate qualitative factors too. So, the strength of this study over previous studies such as Al Hallak et al (2019), Shafiei Nikabadi andHakaki (2019) and Shiboud and Assaf (2019), Ojugbele and Bodhanya (2015), Lisse (2014), Block and Pickl (2014) is the formulation of qualitative factors. Another positive point of this study is that it could find roots of consequences and make comprehensible offers for top managers.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…However, Dahlström et al (2018) showed that the excessive use of outsourcing in public services can decrease quality. For these reasons, several authors have proposed that service performance evaluations are already outsourced in the public sector (Ahimbisibwe et al, 2012;Cordella & Willcocks, 2010;Duhamel et al, 2014;Ojugbele & Bodhanya, 2015;Rönnbäck & Witell, 2009;Waal & Kerklaan, 2010).…”
Section: Literature Overviewmentioning
confidence: 99%